Implementasi Pastoral Konseling Dalam Rangka Pengabdian Kepada Masyarakat: Refleksi Pengalaman di Jemaat Efrata Buha Tagulandang - Inri Neunatalia Deasy Wagey; Tirza Prily Supit (PT. Giat Konseling Nusantara, 2026)
This article presents a reflective experience of implementing pastoral counseling as a form of Community Service (PKM) at Jemaat Efrata Buha, Tagulandang. Pastoral counseling is a ministry that integrates faith and psychological dimensions in helping individuals navigate life's challenges. This PKM activity was conducted in response to the genuine need of the congregation for structured and professional pastoral accompaniment. Methods employed include pastoral interviews, individual and group counseling, and participatory observation. Results demonstrate that the pastoral counseling approach produced positive impacts on the spiritual and psychological conditions of the congregation. Furthermore, this activity affirms the relevance of pastoral counseling as a contextual PKM model within church settings. This article also presents a critical reflection on the strengths, weaknesses, and implications of the activity for the future development of church pastoral ministry.